1983
DOI: 10.1016/0014-5793(83)80482-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic acid mimicks the muscarinic action of acetylcholine in cultured bovine chromaffin cells

Abstract: In cultured bovine chromaffin cells, acetylcholine as well as muscarine stimulated the 32Pi incorporation into phosphatidic acid, induced the efflux of 45Ca2+ from prelabelled cells, and, in parallel, elevated intracellular cyclic GMP content. Phosphatidic acid added to the medium also stimulated the efflux of 45Ca2+ and the synthesis of cyclic GMP in the cells in the same fashion as muscarinic agents, whereas it did not induce the secretion of catecholamines indicating that the effect of phosphatidic acid is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

1984
1984
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…4), whereas exogenously added phospholipase C was unable to do so. Furthermore, the addition of exogenous PA to CTLL-2 cells clearly shifted the dose-response curve of IL-2 to lower Although, PA has been shown to be a calcium ionophore for some cells [2S, [35][36][37], the calcium ionophore A23187 was unable to induceTcel1 proliferation, either alone or in the presence of low doses of IL-2. Furthermore, the addition of PA (even at 50 vg/ml) did not cause an increase in intracellular Ca2+, suggesting that PA activity is not merely due to an increase in the intracellular Ca2+ (data not shown).…”
Section: Induction Of T Cell Proliferation By Pamentioning
confidence: 99%
“…4), whereas exogenously added phospholipase C was unable to do so. Furthermore, the addition of exogenous PA to CTLL-2 cells clearly shifted the dose-response curve of IL-2 to lower Although, PA has been shown to be a calcium ionophore for some cells [2S, [35][36][37], the calcium ionophore A23187 was unable to induceTcel1 proliferation, either alone or in the presence of low doses of IL-2. Furthermore, the addition of PA (even at 50 vg/ml) did not cause an increase in intracellular Ca2+, suggesting that PA activity is not merely due to an increase in the intracellular Ca2+ (data not shown).…”
Section: Induction Of T Cell Proliferation By Pamentioning
confidence: 99%
“…Moreover, in bovine chromaffin cells and rat liver cells, an increase in the intracellular Ca2+ level may be effected by either muscarinic stimulation or calcium ionophore treatment, resulting in an eleva tion of cGMP content. One interpretation of this find ing is that an increase in guanylate cyclase activity takes place after increased uptake of Ca2+ [17,18]. Therefore, a Ca2+-mediated cell-activating process may be caused by an increase in cGMP content and the A/G ratio seems to be an indication of the hista mine release response.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that cholinergic agonists stimulate release of Ca from intracellular stores via the phosphatidyl inositol breakdown pathway. There is controversy as to whether this is due to muscarinic stimulation (Ohsako and Deguchi, 1983;Schneider, 1985, 1986;Forsberg et al, 1986) or both, nicotinic and muscarinic stimulation (Eberhard and Holz, 1987). These authors agree, however, that Ca release from internal stores is small in bovine chromaffin cells and not sufficient to evoke secretion.…”
Section: The Evidence For Cosecretion Of Calcium and Catecholaminementioning
confidence: 99%
“…Secretory vesicles, during exocytosis, fuse with the plasma membrane and their inner space becomes continuous with the extracellular space. Uptake of Ca into secretory vesicles and discharge by exocytosis as a pathway of Ca export has not been investigated in detail. In studies attempting to characterize the mechanism of the termination of catecholamine release, stimulated Ca export has been interpreted solely as Ca efflux across the plasma membrane (Ohsako and Deguchi, 1983;Wada et al, 1984;Morita et al, 1987).…”
mentioning
confidence: 99%